A proposed integrated Islamic crowdfunding - microfinance (IICM) model for poverty reduction: a case study of Indonesia - Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hassanudin; Allah Pitchay, Anwar (International Research Centre of Islamic Economics and Finance(IRCIEF), Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2018)
Poverty is a complex, multi-dimensional phenomena that has captured the attention of numerous scholars and agencies globally including OIC member countries. In order to address this alarming poverty problem, some of the OIC countries have adopted the institution of microfinance as a solution, including in Indonesia. In spite of its expansion, microfinance continues to face the problem of accessing affordable financing. Hence, this paper aims to attempt to offer a viable alternative model of source of financing which is known as Integrated Islamic Crowdfunding- Microfinance (IICM) model for microfinance clients in Indonesia. In order to achieve this objective, literature on the issues of accessing to finance faced by microfinance clients and crowdfunding are reviewed critically and used in the attempt of proposing an alternative model. The proposed model will assist microfinance institutions and clients of Indonesia in identifying sustainable financing source and a viable alternative model for poverty alleviation. Through this, Indonesia will play a leading role among the Muslim countries with the noble idea of Islamic crowdfunding and microfinance in poverty alleviation agenda. It enables policy makers to plan more effective plans/strategies to enhance the potential of Islamic crowdfunding among the Muslim countries in addressing issue of poverty in general.